Efectividad del programa educativo en el nivel de conocimiento de las enfermeras sobre nutrición parenteral en la unidad de cuidados intensivos neonatal Trujillo - Rocca Acevedo, Roxana Marilú (2019)
This Pre-experimental research with pre-test and post-test was applied to nurses of the Neonatal Intensive Care Unit of the Víctor Lazarte Echegaray Hospital, between September and November 2016, in order to determine the effectiveness of the educational program at the level of knowledge of nurses on Neonatal Parenteral Nutrition. The sample consisted of 24 nurses. For the data collection, the instrument was used: level of knowledge of nurses on administration and manipulation of parenteral nutrition, the information obtained being processed and analyzed by: the statistical test “student's t”. The results found that prior to the application of the educational program, 41.7 percent of nurses obtained a low level of knowledge, 33.3 percent of nurses obtained a medium level of knowledge and 25 percent of nurses reached a level of high knowledge After applying the educational program, 100 percent of nurses reached a high level of knowledge. It was concluded that the educational program was effective in improving the level of knowledge of nurses, obtaining a student's t-value of -10,887 with a probability of 0.000 being highly significant.